Metabolomic Analysis of the Takifugu Obscurus Gill under Acute Hypoxic Stress - Huakun Zhang; Ziwen Hu; Run Li; Yaohui Wang; Jinxu Zhou; Hao Xu; Guan Wang; Xuemei Qiu; Xiuli Wang (Animals, 2022)
Takifugu obscurus has relatively small gills and gill pores. Consequently, a relatively low respiratory capacity. This fish is thus easily negatively affected by the low levels of dissolved oxygen (DO) that are common in high-intensity aquaculture. In order to clarify the mechanisms underlying the hypoxia response of T. obscurus, we used liquid mass spectrometry (LC–MS) to identify and quantify the metabolites present in the T. obscurus gill under the following conditions: normoxia (DO, 7.0 ± 0.2 mg/L), hypoxia (DO, 0.9 ± 0.2 mg/L), and reoxygenation (4, 12, and 24 h after return to normoxia conditions). We identified a total of 821 and 383 metabolites in the gill in positive and negative ion modes, respectively. Of the metabolites identified in positive ion mode, 136 were differentially abundant between hypoxia and all other conditions; of the metabolites identified in negative ion mode, 34 were differentially abundant between hypoxia and all other conditions. The metabolites which were differentially abundant under hypoxia primarily included glycerol phospholipids, fatty acids, hormones, and amino acids as well as related compounds. The pathways which were significantly enriched in the differentially abundant metabolites included the lipid metabolism, amino acid metabolism, purine metabolism, FoxO signaling pathway, and mTOR signaling pathway. Our results help to clarify the mechanisms underlying hypoxia tolerance and to identify hypoxia-related metabolites, as well as to highlight potential research targets for the development of hypoxic-tolerant strains in the future.